Mycotic Aneurysm with Iliac Artery-Colonic Fistula - Le Viet Dung; Ma Mai Hien; Dang-Thi Bich Nguyet; Thieu-Thi Tra My; Nguyen Minh Duc (Case Reports in Medicine)
Although mycotic (infected) aneurysms are uncommon, they can affect any artery. The most frequently involved vessel is the aorta as well as femoral and cerebral arteries. A vascular-colonic fistula from infected aneurysms is even rarer, which remains a challenge for diagnosis and treatment. In this case report, we aimed to illustrate an 89-year-old man presenting initially with an aneurysm of the right common iliac artery. Forty days later, this lesion was infected and produced fresh blood in the rectum and sigmoid colon observed by colonoscopy. The final diagnosis of this case was a right common iliac artery aneurysm-colonic fistula due to infection. The patient was successfully diagnosed and treated with surgery at our hospital.